Az egyházak megjelenítése a csehszlovákiai magyar általános iskolai történelemtankönyvekben (1948-1989) = The representation of churches in Hungarian primary school history textbooks in Czechoslovakia (1948-1989) - Bese László (Belvedere Meridionale Szeged, 2023)
In the decades of socialism, history teaching, including history textbooks, was strongly at the service of political propaganda. This was no different in Czechoslovakia, where the Hungarian-language schools could only use the mirror translations of the centrally approved Czechoslovak textbooks. Under the influence of party-state propaganda, a particular form of narrative emerged, which operated essentially with enemy images. One of the typical images of the enemy of the party-state in the mainstream was the church itself, and so the church institution became one of the central (negative) characters in history textbooks. From antiquity onwards, textbook writers in the period under study emphasised what they saw as the church’s harmful activities in society, which were primarily aimed at legitimising the activities of oppressive and exploitative social groups. The aim of this paper is to show the characteristics of this textbook representation and how it changed in the decades of socialism as a result of various current political events.